Nothing new in marketing communication of e-cigarettes: The new wave of fake news - Iztok Sila (Agora International Journal of Economical Sciences (AIJES), 2024)
The tobacco industry is using the same methods of persuasion as they were doing since the start of advertising cigarettes and other tobacco products in 1914. Producers of tobacco products have been accused of spreading misinformation and fake news since the 1980. Main objective of our paper is to describe the evolution of "fake" marketing communication, especially of e-cigarettes - lately the deceptive strategies of e-tobacco companies in their advertising campaigns, where they minimize the dangers of smoking and portray it as a beneficial or attractive practice are coming under the control of the relevant institutions. Since the e-tobacco companies are using all the modern means and platforms of communication, especially young generations are quite successfully targeted. Results of desk research will be presented as well as some of the activities performed by state owned, and private institutions aimed to prevent harmful and shameless spreading of this conflicting information.
Keywords: 330